Self-Efficacy as a Predictor of Readiness for Change in Digital Enterprise Employees - Ayu Amalia, Hana; Endang Kusmaryani, Rosita (Lafadz Jaya Publisher, 2024)
Every company must adapt to the digital era, and a crucial strategy for achieving this is preparing for change. Employees who are ready for change tend to operate more effectively. This research aims to determine whether self-efficacy predicts readiness for change among digital enterprise employees. The study used a quantitative approach with a survey design. The sample comprised 106 digital enterprise employees. Data were collected using a 25-item Readiness to Change Questionnaire and a 10-item General Self-Efficacy Scale (GSES) instrument. The validity test utilized content and construct validity, ensuring the instruments accurately measure the intended constructs. The reliability test, using Cronbach's Alpha, ranged from 0.592 to 0.955, indicating varying levels of internal consistency, while the reliability of the measurement model (inner model) ranged from 0.773 to 0.961, suggesting high reliability. The results of the hypothesis testing show that (1) self-efficacy is a significant predictor of readiness for change, with a predictive relevance of 30%; (2) self-efficacy significantly influences the appropriateness dimension, with an effective contribution of 47.1%; (3) self-efficacy is a significant predictor of the management support dimension, with an effective contribution of 46%; (4) self-efficacy significantly predicts the change efficacy dimension, with an effective contribution of 47.9%; (5) however, self-efficacy is not a significant predictor of personal benefits. These findings underscore the importance of self-efficacy in enhancing employees' readiness for change within digital enterprises. Companies should focus on boosting employees' self-efficacy to improve their adaptability and effectiveness in the face of digital transformation. By recognizing and fostering the key dimensions influenced by self-efficacy, organizations can better support their workforce during periods of change. Overall, this research contributes to the understanding of psychological factors that facilitate successful change management in the digital era.